Polymorphism of inflammatory genes and arsenic methylation capacity are associated with urothelial carcinoma - Wu, Chia-Chang; Huang, Yung-Kai; Chung, Chi-Jung; Huang, Chao-Yuan; Pu, Yeong-Shiau; Shiue, Horng-Sheng; Lai, Li-An; Lin, Ying-Chin; Su, Chien-Tien; Hsueh, Yu-Mei (Toxicology and applied pharmacology, 2013)
Chronic exposure to arsenic can generate reactive oxidative species, which can induce certain proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6) and interleukin-8 (IL-8). TNF-α, IL-6 and IL-8 have been shown to be involved in the development and progression of various cancers, including bladder cancer. This study aimed to investigate the joint effect of the polymorphism of TNF-α −308 G/A, IL-6 −174 G/C, IL-8 −251 T/A and urinary arsenic profiles on urothelial carcinoma (UC) risk. This study evaluated 300 pathologically-confirmed cases of UC and 594 cancer-free controls. Urinary arsenic species were detected using high-performance liquid chromatography-linked hydride generator and atomic absorption spectrometry. The polymorphism of TNF-α −308 G/A, IL-6 −174 G/C and IL-8 −251 T/A was determined using polymerase chain reaction-restriction fragment length polymorphism. The joint effects on UC risk were estimated by odds ratios and 95% confidence intervals using unconditional logistic regression. We found that the TNF-α −308 A/A and IL-8 −251 T/T polymorphisms were significantly associated with UC. Moreover, significant dose–response joint effect of TNF-α −308 A/A or IL-8 −251 T/T genotypes and arsenic methylation indices were seen to affect UC risk. The present results also showed a significant increase in UC risk in subjects with the IL-8 −251 T/T genotype for each SD increase in urinary total arsenic and MMA%. In contrast, a significant decrease in UC risk was found in subjects who carried the IL-8 −251 T/T genotype for each SD increase in DMA%. •Joint effect of the TNF-α -308 A/A genotype and urinary total arsenic affected UC.•Joint effect of the IL-8 -251 T/T genotype and urinary total arsenic affected UC.•Urinary total arsenic level, TNF-α -308 A/A and IL-8 -251 T/T genotype affected UC.